Instagram as a Marketing Tool for Smart Tourism Businesses: An Analysis - Kale, Sachin S.; Borlikar, Rohit R.; Lama, Rinzing (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The purpose of this study is to examine how tourism businesses use Social Networking Sites (SNS) to promote their products with building a network ecosystem. The findings show that the majority of tourism businesses use online platforms like Facebook, Instagram, LinkedIn, and Twitter to engage with the public and provide a varied range of information to develop E-branding. Tourism businesses use specific social media sites, and the level of use of these sites varies depending on the degree of their business. The study also revealed that the social media accounts of tourism businesses follow various other social media accounts to establish a network as a part of smart tourism ecosystem. The study’s findings will help improve the use of social networking sites for online content production, social media campaign management, tourism marketing, branding, and promotion of tourism businesses. Theoretical contributions and managerial implications of this study are discussed.